2007
DOI: 10.1088/0034-4885/71/1/016102
|View full text |Cite
|
Sign up to set email alerts
|

Electron holography—basics and applications

Abstract: Despite the huge progress achieved recently by means of the corrector for aberrations, allowing now a true atomic resolution of 0.1 nm, hence making it an unrivalled tool for nanoscience, transmission electron microscopy (TEM) suffers from a severe drawback: in a conventional electron micrograph only a poor phase contrast can be achieved, i.e. phase structures are virtually invisible. Therefore, conventional TEM is nearly blind for electric and magnetic fields, which are pure phase objects. Since such fields p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
220
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(224 citation statements)
references
References 85 publications
(89 reference statements)
4
220
0
Order By: Relevance
“…As discussed below, using electron beam from Al gate as reference wave will not confuse the analysis of charge-induced phase modulation in the high-k dielectric film. It also avoids the risk of stray field disturbance in the conventional scheme where the phase of the vacuum reference wave could be distorted by the stray field of gate or electrode 49 but the phase resolution is sacrificed because of the coherence deterioration of the penetrating wave 50 . Thus, at least 20 retrieved phase images for each bias were averaged to obtain the final phase distribution, including 0 V image, which was subtracted as the 'background' from the phase maps under bias.…”
Section: Methodsmentioning
confidence: 99%
“…As discussed below, using electron beam from Al gate as reference wave will not confuse the analysis of charge-induced phase modulation in the high-k dielectric film. It also avoids the risk of stray field disturbance in the conventional scheme where the phase of the vacuum reference wave could be distorted by the stray field of gate or electrode 49 but the phase resolution is sacrificed because of the coherence deterioration of the penetrating wave 50 . Thus, at least 20 retrieved phase images for each bias were averaged to obtain the final phase distribution, including 0 V image, which was subtracted as the 'background' from the phase maps under bias.…”
Section: Methodsmentioning
confidence: 99%
“…(1), C E is a constant that depends on the microscope accelerating voltage and takes a value of 6.53 Â 10 6 rad V À1 m À1 at 300 kV, while V and A z are the electrostatic potential and the component of the magnetic vector potential in the electron beam direction z, respectively. [14][15][16] Recently, Beleggia et al 17 showed that the magnitude and direction of the electric field around the tip of an electrically biased ellipsoidal metallic needle can be measured by fitting simulations based on theoretical models for the charge density distribution along the needle to electron holographic phase images or Lorentz micrographs. Here, we use a modelindependent approach 18 to determine the charge density distribution along an electrically biased Fe APT needle directly from recorded phase images.…”
Section: Introductionmentioning
confidence: 99%
“…In the image plane, a hologram is formed, from which φ PP can be extracted. Details on the experimental procedure and the hologram evaluation are described in review articles [23,24]. substrate.…”
Section: Methodsmentioning
confidence: 99%